1998
DOI: 10.1021/ja981888i
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Hot Spots for DNA Damage by One-Electron Oxidation: Efficacy of GG Doublets and GGG Triplets as a Trap in Long-Range Hole Migration

Abstract: There has been much current interest in the long-range oxidative damage to DNA through the DNA duplex caused by one-electron oxidations. 1 Hole (radical cation) migration through the DNA duplex has been suggested to play a crucial role in mutagenesis and carcinogenesis caused by carcinogenic agents, ionizing radiation, and high-intensity laser irradiation. 1,2 As is well-known, guanine (G) is the most easily oxidized base, 3 and the electron-loss center created in duplex DNA ultimately ends up at G residues v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
447
3
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 372 publications
(496 citation statements)
references
References 29 publications
43
447
3
3
Order By: Relevance
“…The enhanced rate constants of oxidation at GG and GGG sequences are consistent with the Saito model. 11,19,20 The k G value for sequence 1d with isolated guanines near the ends in AGA sequence contexts are similar in value to k G in the GGG sequence context in duplex 5d. We attribute this large value of k G to end effects rather than to sequence effects (AGA vs. TGT) for the following reasons.…”
Section: Dependence Of Decay Rates Of Bpt •+ Radicals On Dna Concentrmentioning
confidence: 69%
See 4 more Smart Citations
“…The enhanced rate constants of oxidation at GG and GGG sequences are consistent with the Saito model. 11,19,20 The k G value for sequence 1d with isolated guanines near the ends in AGA sequence contexts are similar in value to k G in the GGG sequence context in duplex 5d. We attribute this large value of k G to end effects rather than to sequence effects (AGA vs. TGT) for the following reasons.…”
Section: Dependence Of Decay Rates Of Bpt •+ Radicals On Dna Concentrmentioning
confidence: 69%
“…In early experiments it was shown that photoexcitation of DNA in its normal B-type double helical form by intense nano-or picosecond 266 nm laser pulses induces a greater damage of guanines positioned on the 5′-side of purine bases, especially adjacent to guanine, than on guanines adjacent to pyrimidines. 7 This selectivity of G oxidation in different sequence context has been also observed employing one-electron oxidants generated by photosensitization of metal complexes, 3,8 anthraquinones, 4,9 naphthalimides, 10 riboflavin (RF), 11,12 4′-pivaloyl derivatives, 13,14 cyanobenzoyl and cyanobenzophenone substituted 2′-deoxyuridine 15,16 and other chemical one-electron oxidants. 17, 18 Saito and co-workers have shown that the enhancement of oxidative guanine damage increases with the number of contiguous guanines according to 5′-G < 5′-GG < 5′-GGG and that this phenomenon is correlated with the calculated gas phase ionization potentials (IP) for guanines in different sequence contexts.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations